Importance of vaccine coverage against poliomyelitis (International Seven Journal of Health Research, 2024)
Poliomyelitis is an acute contagious viral disease that can affect children and adults, causing sequelae, especially in the most severe cases. There is no specific treatment, but prevention is extremely important. The study was exploratory in nature, through a literature review based on references published in Scielo, Google Scholar and VHL. Using a qualitative, descriptive and exploratory methodology, the aim was to educate the population of a Basic Health Unit (BHU) in a municipality in the midwest of Santa Catarina about the importance of vaccinating against Poliomyelitis, as well as the consequences of the disease, given that the BHU's vaccination coverage is below the parameters set by the Ministry of Health (MoH). The extension actions to achieve this goal were orientations at the UBS in question, involving a group of family members who accompanied the children to medical appointments. It can be concluded that the population is unaware of the seriousness of this disease, and that various diseases that used to affect the population very aggressively can now be considered eradicated, such as polio if we achieve good vaccination coverage.